Comparison of the pharmacokinetics, safety, and immunogenicity of MSB11022, a biosimilar of adalimumab, with Humira® in healthy subjects. (28th July 2016) - Hyland, Elizabeth; Mant, Tim; Vlachos, Pantelis; Attkins, Neil; Ullmann, Martin; Roy, Sanjeev; Wagner, Volker
Abstract : Aims: The aim of the study was to compare the pharmacokinetics (PK), safety and tolerability of the proposed adalimumab biosimilar MSB11022 (Merck) with Humira ® (AbbVie), sourced from both the US (US reference product [US‐RP]) and Europe (European reference medicinal product [EU‐RMP]). Methods: In this phase 1 double‐blind, parallel group trial (EMR200588‐001), 213 healthy volunteers were randomized 1 : 1 : 1 to receive a single dose (40 mg) of MSB11022, US‐RP or EU‐RMP in order to achieve 80% power assuming a 5% difference among groups and a 10% dropout rate. Following a preplanned blinded sample size re‐assessment after more than 50% of the originally planned subjects had been observed, the sample size was increased to 237 (79 per arm) to ensure 213 completers. Primary PK endpoints analyzed by non‐compartmental methods, were area under the curve (AUC) from time 0 extrapolated to infinity (AUC(0, ∞)), maximum observed concentration ( C max ), and AUC from time 0 to the last quantifiable concentration (AUC(0, t last )). PK equivalence was declared if the 90% CI for the test : reference ratio lay within the 80–125% equivalence margin. Bioequivalence was demonstrated if all three PK parameters met the PK equivalence criteria. Safety and tolerability were also evaluated. Results: Mean serum concentration–time profiles for the three treatments were similar. MSB11022 demonstrated PK equivalence to US‐RP and EU‐RMP for all primary endpoints. The geometric means of AUC(0, ∞), C max and AUC(0, t last ) following a single dose of MSB11022 were 2276.05 μg ml –1 h, 3.44 μg ml –1 and 1983.90 μg ml –1 h, respectively. Adverse events (AEs) were similar across all groups, with treatment‐emergent AEs (TEAEs) reported by 62.8%, 56.3% and 62.0% of subjects within the MSB11022, US‐RP and EU‐RMP groups, respectively. Most of the TEAEs were considered mild and unrelated to study drug. No deaths or severe AEs related to the study drug were reported. Conclusions: Bioequivalence between MSB11022, US‐RP and EU‐RMP was demonstrated. Safety, tolerability and immunogenicity profiles were similar between subjects receiving MSB11022 and US‐RP or EU‐RMP. These data support the further clinical evaluation of MSB11022 as a proposed biosimilar of adalimumab.